IDENTIFY CONNECTIVITY GRAPH USING A MODIFIED PRÜFER’S ALGORITHM LABELLING TREES - Al Aiyub; Mahyus Ihsan; Rahma Zuhra (Universitas Syiah Kuala, 2013)
Connectivity of graph easily can be given when we see it with the bare of eyes, but needs an algorithm that can assure the connectivity in computerization. Some graphs require the connectivity in their definitions, such as Hamiltonian graph, Eulerian graph and tree. The connectivity become important in order to solve any of graphs' problems by using computer technology. Most of the algorithm cannot run perfectly, if the graph which is given was not connected. It is happened to Djikstra and Prufer graphs for example. However, this study will provide the solution by modifying Prufer algorithm to show the connectivity in the graph.